2015 IEEE 16th International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM) 2015
DOI: 10.1109/wowmom.2015.7158123
|View full text |Cite
|
Sign up to set email alerts
|

Mobile HTTP-based streaming using flexible LTE base station control

Abstract: This paper investigates the advantage of adopting a flexible resource control scheme when performing HTTP-based adaptive streaming across LTE systems. To guarantee video fluidity, mobile video streaming is known to require a large bandwidth overhead with respect to the net encoded video rate. The quality of a received video stream is impacted by variations in the size of the transmitted video packets (chunks), and by statistical fluctuations in the data rate at which the allocated downstream wireless channel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Each version is encoded for reception at a prescribed targeted video quality level, and is accordingly characterized by its specific flow bit rate. Previous works (e.g., [7], [8]) have shown that by using resource allocation schemes that are executed by a manger that resides at the cellular eNB side or at a central Resource Manager (RM), one can provide effective QoE support of video streaming at the video users while simultaneously providing for efficient utilization of available wireless resources. In this work, we extend this approach by considering a heterogeneous cellular layout (HetNet) that includes micro and macro cells.…”
Section: System Architecture and Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each version is encoded for reception at a prescribed targeted video quality level, and is accordingly characterized by its specific flow bit rate. Previous works (e.g., [7], [8]) have shown that by using resource allocation schemes that are executed by a manger that resides at the cellular eNB side or at a central Resource Manager (RM), one can provide effective QoE support of video streaming at the video users while simultaneously providing for efficient utilization of available wireless resources. In this work, we extend this approach by considering a heterogeneous cellular layout (HetNet) that includes micro and macro cells.…”
Section: System Architecture and Assumptionsmentioning
confidence: 99%
“…We have then considered different quantization levels (namely 25, 30 and 35) corresponding to the quality levels q = 2, 3 and 4. Moreover, the videos are characterized by different encoding bit rates and different Peak Signal to Noise Ratios (PSNRs), 7 which are summarized in Tab. 5.…”
Section: Adopted Real Video Tracesmentioning
confidence: 99%
See 2 more Smart Citations
“…Encoder settings and resulting video rate R(q) relevant to quality q are summarized in TABLE I [21].…”
Section: Video Coding Modelsmentioning
confidence: 99%